(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
Now-a-days air pollution is one of the most important concern of the world. Air pollution may evolve from anthropogenic or natural sources. Air pollutants of atmospheric substances like CO, CO2, SO2, NO2, and O3 suspended particulate matter (SPM), repairable suspended particulate matter (RSPM), and volatile organic compounds (VOCs) have a great effect on the people health. Most of the major cities in developing countries and most cities of the developed countries are suffering from it. Thus to develop a real time air quality and pollution monitoring system is critical. We have developed an arduino based air pollution detector which combined a small-sized, minimum-cost sensor to an arduino microcontroller unit. The advantages of the detector, have a reliable stability, rapid response recovery and long-life features. It is affordable, user-friendly, low-cost and minimum-power requirement hardware which is appropriate for mobile measurement, as well as comprehensible data collection. It has a processing software able to analyze, collected quality data with high precision. Simple instrument which can be commercially utilized.